Cold Agglutinin Syndrome and Hemophagocytic Lymphohistiocytosis: An Unusual Combination Caused by Epstein–Barr Virus Infection - Sousa Nunes, B (2024)
Autoimmune hemolytic anemia (AIHA) and hemophagocytic lymphohistiocytosis (HLH) are rare complications of infectious mononucleosis. The authors describe a 12-year-old male with acute infectious mononucleosis, hepatitis, cholestasis, and an autoimmune hemolytic disorder caused by cold agglutinins IgM (anti-i specificity). Clinical deterioration with persistent fever, anemia, and hepatosplenomegaly was consistent with cold AIHA plus concomitant HLH. The patient was treated with corticosteroids and acyclovir, with an uneventful recovery. Although rare, cold agglutinin syndrome and HLH can complicate infectious mononucleosis and should be considered in a patient with clinical deterioration. Corticosteroids are the mainstay treatment of HLH and may be beneficial in infection-associated cold agglutinin syndrome.